Novel chloro-substituted thiophene thiosemicarbazone: Synthesis, crystal structures, DFT analysis and antimicrobial evaluation of its Co(II), Zn(II), Ni (II), and Pd(II) complexes - Dundar, Ozan Ali; Subasi, Elif; Oncuoglu, Serkan; Hizliates, Cevher Gundogdu; Sahiner, Asli; Balci, Ceylan Mutlu (Elsevier, 2026)
Thiosemicarbazones, obtained through the condensation of hydrazine derivatives with carbonyl compounds, constitute an important class of Schiff bases with broad pharmacological potential. In this work, a chloro-substituted thiophene-derived thiosemicarbazone ligand was synthesized from 4-methyl-3-thiosemicarbazide, and its coordination complexes with cobalt(II), zinc(II), palladium(II), and nickel(II) ions were prepared. The synthesized compounds were characterized comprehensively using Fourier Transform Infrared Spectroscopy, Ultraviolet-Visible Spectroscopy, proton Nuclear Magnetic Resonance, mass spectrometry, elemental analysis, molar conductivity, and single-crystal X-ray diffraction. Structural and electronic features were further investigated through density functional theory calculations, which provided insights into orbital distributions, energy gaps, and optimized geometries. Antimicrobial screening demonstrated that the ligand and its metal complexes exhibited significant inhibitory effects against selected bacterial and fungal strains, with enhanced activity observed for the complexes compared to the free ligand. The combined experimental and computational findings highlight the importance of halogen substitution and transition-metal coordination in tuning the biological and electronic properties of thiosemicarbazone derivatives, supporting their potential as promising candidates for future therapeutic development.
Keywords: Metal(II) coordination complexes; Thiosemicarbazone-based Schiff bases; Single-crystal X-ray diffraction; Density functional theory studies; Antimicrobial activity